The synergistic effect of N-doped TiO2-SiO2 nanocatalysts and peroxydisulfate towards improving Bisphenol A photodegradation efficiency - Lê, Minh Viễn (Malaysian NANO-An International Journal, 2022)
TiO2-based photocatalysts have attracted tremendous attention for the degradation of hazardous organic pollutants in sewage. In this work, a series of N-doped TiO2-SiO2 with varying N contents (10N-TS5, 20N- TS5, 30N-TS5) were successfully synthesized via sol-gel method. The physical properties of the catalyst are characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive emission spectroscopy (EDX), UV-visible absorption spectroscopy, and specific surface area (BET) measurements. The photocatalytic activities of as-prepared catalysts were assessed by degrading 10 mg. L-1 Bisphenol A (BPA) under simulated natural light irradiation. The results indicate that the N doping in the TiO2-SiO2 nanostructures can reduce the crystal sizes, improve the BET surface areas, and narrow the band gap energy, thereby enhancing the photocatalytic activity of the materials. The 10N-TS5 exhibits the best photoactivity, which degrades 90.7 % of BPA for 240 min irradiation. Noteworthy, the presence of 2 mM peroxydisulfate (PDS, S2O82-) in the 10N-TS5 reaction system removes completely 10ppm BPA for only 50 min illumination with the rate constant of 10.9×10-2 min-1, 7.8 times higher than that of 10N-TS5 suspension without PDS agent. The N-doped TiO2-SiO2 photocatalyst coupling with PDS provides a promising pathway for environmental remediation.